Associations of experiential avoidance with burnout, wellbeing, and productivity loss among police officers: The mediating role of negative and positive affect. Issue 11 (6th May 2022) - Mojallal, Mahsa; Simons, Raluca M.; Quevillon, Randal P.; Hatwan, Mason L.
Abstract: Objectives: The current study aims to investigate the indirect associations between experiential avoidance (EA) and burnout, wellbeing, and productivity loss (PL) via the mediating role of positive and negative emotions among police officers. Methods: Data were collected on 187 officers (84% male) aged 21–64 years between 2019 and 2020. Participants completed online self‐report measures. Results: EA was indirectly associated with burnout via positive and negative affect. EA was indirectly associated with wellbeing through positive affect, positive affect and burnout, and negative affect and burnout. Finally, EA was indirectly associated with PL via positive affect and burnout, and negative affect and burnout. Conclusion: Results provide support for the role of EA in officers' wellbeing and job performance via increasing negative affect and decreasing positive affect. This highlights the importance of interventions, such as acceptance and commitment therapy that target acceptance and psychological flexibility.